1996
DOI: 10.1111/j.1469-8137.1996.tb04631.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated CO2, O3 and K deficiency on Norway spruce (Picea abies): nutrient supply, content and leaching

Abstract: SUMMARYTwo clones of 5-yr-old Norway spruce {Picea abies [L.] Karst.) were exposed to two atmospheric concentrations of CO2 (350 and 750/^.mol mol"^) and of O3 (20 and 75 nmol mol"^) in a phytotron at the GSFForschungszentrum (Munich) over the course of a single season (April-October). The phytotron was programmed to recreate an artificial climate similar to that at a high elevation site in the Inner Bavarian forest, and trees were grown in 40 1 containers of soil (pH 3-5) fertilized to achieve two levels of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…This is in agreement with most results obtained in other studies of conifers: loblolly pine, Pinus taeda, by Edwards et al (1992); Norway spruce by Ogner (1993), Pfirrman et al (1990, Schätzle et al (1990) and Skärby et al (1995); Silver fir, Abies alba, by Schätzle et al (1990); Red spruce, Picea rubens, by Thornton et al (1992). However, there are also studies that have found changes in the needle nutrient concentrations, for example both Rantanen et al (1994) and Pfirrmann et al (1996) found a decrease of the N concentration in needles of Norway spruce trees after ozone exposure.…”
Section: Mineral Nutrientssupporting
confidence: 91%
See 1 more Smart Citation
“…This is in agreement with most results obtained in other studies of conifers: loblolly pine, Pinus taeda, by Edwards et al (1992); Norway spruce by Ogner (1993), Pfirrman et al (1990, Schätzle et al (1990) and Skärby et al (1995); Silver fir, Abies alba, by Schätzle et al (1990); Red spruce, Picea rubens, by Thornton et al (1992). However, there are also studies that have found changes in the needle nutrient concentrations, for example both Rantanen et al (1994) and Pfirrmann et al (1996) found a decrease of the N concentration in needles of Norway spruce trees after ozone exposure.…”
Section: Mineral Nutrientssupporting
confidence: 91%
“…However, there are also studies that have found changes in the needle nutrient concentrations, for example both Rantanen et al. (1994) and Pfirrmann et al. (1996) found a decrease of the N concentration in needles of Norway spruce trees after ozone exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Information on the effects of CO 2 enrichment different levels of CO 2 , O 3 , nitrogen nutrition and drought. Pfirrmann et al (1996) also used Norway on nutrients other than N or P in herbaceous species is scarce. Reduced concentrations of spruce saplings to investigate the effects of CO 2 enrichment, O 3 and K deficiency on element con-macro-and micronutrients have been reported after exposure to CO 2 enrichment by some authors centrations in fine roots, current year needles and previous-year needles.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this study was to investigate the independent and combined effects of elevated CO 2 and Pfirrmann et al (1996) b Penuelas et al (2001) c Penuelas et al (1997) d Huluka et al (1994) e Heagle et al (1993) elevated O 3 on mineral nutrient cycling in aggrading aspen and birch-aspen stands of the Aspen FACE project in Rhinelander, WI. Elevated CO 2 increased total biomass production by 43% and elevated O 3 decreased it by 17% in this long-term experiment (King et al 2005b).…”
mentioning
confidence: 99%